Intimacy and injury : in the wake of #MeToo in India and South Africa - Falkof, Nicky; Phadke, Shilpa; Roy, Srila (Governing intimacies in the Global South, 2022)
Intimacy and injury offers an original perspective on the #MeToo movement from South Africa and India. It overturns the dominance of western debates on #MeToo by foregrounding diverse southern feminist takes on the possibilities and limits of this movement in the global south.